2011
DOI: 10.1152/ajplung.00126.2010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoptosis by 60% oxygen: a novel pathway contributing to lung injury in neonatal rats

Abstract: During early postnatal alveolar formation, the lung tissue of rat pups undergoes a physiological remodeling involving apoptosis of distal lung cells. Exposure of neonatal rats to severe hyperoxia (≥95% O(2)) both arrests lung growth and results in increased lung cell apoptosis. In contrast, exposure to moderate hyperoxia (60% O(2)) for 14 days does not completely arrest lung cell proliferation and is associated with parenchymal thickening. On the basis of similarities in lung architecture observed following ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…Furthermore, we have shown that levels of supplemental oxygen Ͼ60% cause apoptosis in human fetal ASM cells in contrast to the ASM proliferation observed at lower levels of oxygen exposure (6). This is consistent with the inhibition of apoptosis observed in lung cells of neonatal rats exposed to 60% compared with 95% oxygen (23). We therefore sought to test the hypothesis that modest hyperoxic exposure would cause a greater increase in airway reactivity compared with severe hyperoxia and that this response would be sustained beyond completion of hyperoxic exposure.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, we have shown that levels of supplemental oxygen Ͼ60% cause apoptosis in human fetal ASM cells in contrast to the ASM proliferation observed at lower levels of oxygen exposure (6). This is consistent with the inhibition of apoptosis observed in lung cells of neonatal rats exposed to 60% compared with 95% oxygen (23). We therefore sought to test the hypothesis that modest hyperoxic exposure would cause a greater increase in airway reactivity compared with severe hyperoxia and that this response would be sustained beyond completion of hyperoxic exposure.…”
supporting
confidence: 85%
“…Prior studies have reported on the role of 95-100% hyperoxic exposure in promoting apoptosis in the mesenchyme of the developing lung (4). In contrast, more recent data have proposed that 60% oxygen exposure for 14 days may inhibit apoptosis and contribute to parenchymal thickening in neonatal rat lungs (23). In a prior study we sought to determine the role of various oxygen concentrations in inducing proliferation of human fetal ASM cells under in vitro conditions (6).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ARDS generally require positive-pressure ventilation with high fractions of inspired oxygen causing hyperoxia in the lung. Hyperoxia may also contribute to lung injury primarily by initiating ROS generation (8,117) and activating the inflammasome (122), leading to altered mechanical properties (198) and apoptosis (23,144,148,263) of alveolar epithelial cells. As a consequence of protective ventilation with low tidal volumes, a number of patients display elevated levels of CO 2 , termed permissive hypercapnia.…”
Section: Noninflammatory Mediators Of Alimentioning
confidence: 99%
“…Pathogen-free timed-pregnant Sprague-Dawley rats (250-275 g) were obtained from Charles River (St-Constant, Senneville, QC, Canada). Rat pups (10-12/litter) were exposed to air or 60% O 2 in paired chambers (Biospherix, Lacona, NY, USA) for up to 14 days, as previously described [9,[12][13][14][15][16][17][18][19]. Pups were delivered inside the chambers.…”
Section: In Vivo Interventionsmentioning
confidence: 99%
“…Neonatal rats exposed to 60% O 2 from birth for 14 days develop a chronic neonatal lung injury with many of the pathological features observed in human BPD. These include impaired alveologenesis, Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/freeradbiomed parenchymal thickening, and evidence of pulmonary hypertension with small vessel pruning [8][9][10][12][13][14][15][16][17][18][19][20]. Marked immunoreactivity of lung tissue for nitrotyrosine is evident following exposure to 60% O 2 [13], which is prevented by concurrent treatment with a peroxynitrite decomposition catalyst [18].…”
Section: Introductionmentioning
confidence: 99%